Feasibility, acceptability, and potential effectiveness of an online expressive writing intervention for COVID-19 resilience. (November 2021) - Bechard, Elizabeth; Evans, John; Cho, Eunji; Lin, Yufen; Kozhumam, Arthi; Jones, Jill; Grob, Sydney; Glass, Oliver
Abstract: Background & purpose: The COVID-19 pandemic has negatively impacted mental health in the general population. In this trial, our objective was to assess whether a 6-week expressive writing intervention improves resilience in a sample from the general population in the midst of the COVID-19 pandemic. Materials & methods: This 6-week trial was conducted online. Eligible participants (n=63) were a sample of adults who self-identified as having been significantly affected by the COVID-19 pandemic. Primary outcome: Connor-Davidson Resilience Scale (CD-RISC). Secondary outcomes: Perceived Stress Scale – 10-Item (PSS-10); Center for Epidemiologic Studies Depression Scale – Revised (CESD-R); Post-Traumatic Growth Inventory (PTGI). Results: Resilience measures (CD-RISC) increased from baseline (66.6 ± 14.9) to immediately post-intervention (73.0 ± 12.4; p=0.014; Cohen's d =0.31), and at a 1- month follow-up (72.9 ± 13.6; p=0.024; Cohen's d =0.28). Across the same timepoints, perceived stress scores (PSS-10) decreased from baseline (21.8 ± 6.6) to immediately post-intervention (18.3 ± 7.0; p=0.008; Cohen's d =0.41), and at the 1- month follow-up to (16.8 ± 6.7; p=0.0002; Cohen's d =0.56). Depression symptoms (CESD-R) decreased from baseline (23.3 ± 15.3) at 6 weeks (17.8 ± 15.4; p=0.058; Cohen's d =0.22), and 10 weeks (15.5 ± 12.7; p=0.004; Cohen's d =0.38). Posttraumatic growth (PTGI) increased from baseline (41.7 ± 23.4) at 6 weeks (55.8 ± 26.4; p=0.004; Cohen's d =0.44), and at the 1-month follow-up (55.9 ± 29.3; p=0.008; Cohen's d =0.49). Conclusion: An online expressive writing intervention was effective at improving resilience in the midst of the COVID-19 pandemic. NCT#: NCT04589104 Highlights: Expressive writing may improve resilience in those impacted by the COVID-19 pandemic. Expressive writing promotes post-traumatic growth during the COVID-19 pandemic. Online expressive writing was feasible and well-accepted during the COVID-19 pandemic.